(untitled) (Research, Society and Development, 2022)
Periodontitis is a non communicable chronic inflammatory pathology of microbial etiology, which results in loss of periodontal attachment. Rheumatoid arthritis -RA- is a chronic systemic autoimmune disease. Periodontitis and RA share similar humoral and cellular immune responses and a common immunogenic profile; both conditions can bidirectionally influence the systemic burden of inflammation. Nonsurgical periodontal treatment -NSPT- for periodontitis may have beneficial effects on RA disease activity. Objective: to identify the available scientific evidence on the impact of NSPT in periodontitis on the control of RA disease activity. Methodology: narrative review of the literature; 10 publications in English -from 2009 to 2021- were selected from the PUBMED, COCHRANE and WILEY scientific databases; information on the impact of NSPT on periodontitis in patients with RA was identified; the results were expressed in text and a summary table. Results: The NSPT of periodontitis had an impact on the decrease in the activity of the RA disease. The most used disease activity index in patients with RA was the DAS28. NSPT improved the clinical parameters of periodontitis. For all this, dental care and periodontal treatment are necessary in the multidisciplinary management of patients with RA.